Генетичні варіанти мікросомального тригліцеридтранспортного протеїну як причина стеатозу печінки, абеталіпопротеїнемії - Панчишин, Ю.М.; Комариця, О.Й. (Медична гідрологія та реабілітація, 2011)
Microsomal triglyceride transfer protein (MTTP) is necessary for the assembly and secretion of VLDL and when the protein is not functional, such as in abetalipoproteinaemia. MTTP may play a central role in HCV-related steatosis, being modulated by different genotype-specific mechanisms, mainly hyperinsulinemia in non-HCV-3 patients, and more profound and direct virus-related effects in HCV-3- infected individuals. Abetalipoproteinemia is a rare autosomal recessive disease characterized by low lipid levels and by the absence of apoB-containing lipoproteins. It is the consequence of microsomal triglyceride transfer protein deficiency.